PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SANY TOGA GEMILANG - Overagus Sibagariang; Togi Manalu; Wulan Sari Girsang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Employee performance is the level of success of employees in carrying out their duties. Factors that influence employee performance are training and discipline. Training is an activity prepared by management to improve the employees’ skills and abilities to produce high performance. Discipline is the awareness and availability of a person to obey all applicable rules and social norms. The employee’s performance decreases due to the poor discipline and inappropriate training programs. PT. Sany Toga Gemilang is engaged in the plastic industry. The research method used is a quantitative approach, the type of research used is quantitative descriptive. Data collection is done by having interviews, questionnaires and documentation studies. Analysis of the data used is multiple linear regressions. The population is all employees (186 people). Slovin formula was used in determining the research sample, where 127 people were obtained as the study sample, while for testing the validity taken a sample of 30 people outside the study sample. The results showed that training and discipline simultaneously and partially have a positive and significant effect on employee’s performance with a determinant coefficient of 0.767 or 76.7%, while the remaining 23.3% was not examined. The conclusion of the study is that simultaneously and partially training and discipline have a significant effect on employee’s performance at PT. Sany Toga Gemilang.